Konsep Pembiayaan Mudharabah pada KJKS BMT Salafiyah - Ali Burhan; Diana Alfianti (Al-Adillah: Jurnal Hukum Islam, 2022)
Sharia Financial Institutions, especially BMT Salafiyah, in their activities refer to Islamic Law, and in their activities there are administrative costs and the obligation to include guarantees in submitting financing and paying stamp duty provided by BMT Salafiyah. Based on the implementation and discussion, it was found that in the Mudharabah financing mechanism there are administrative costs and paying stamp duty provided by BMT Salafiyah as well as guarantees requested by BMT Salafiyah for prospective members. Meanwhile, the benefit of Mudharabah for BMT Salafiyah is to enjoy an increase in profit sharing when the customer's business profits increase, while for customers or members it is able to expand and increase business volume.